2022
DOI: 10.1038/s41598-022-22659-2
|View full text |Cite
|
Sign up to set email alerts
|

Surface properties-dependent antifungal activity of silver nanoparticles

Abstract: Silver nanoparticles (AgNPs) exhibit unusual biocidal properties thanks to which they find a wide range of applications in diverse fields of science and industry. Numerous research studies have been devoted to the bactericidal properties of AgNPs while less attention has been focused on their fungicidal activity. Our studies were therefore oriented toward determining the impact of AgNPs characterized by different physicochemical properties on Fusarium avenaceum and Fusarium equiseti. The main hypothesis assume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 73 publications
1
20
0
Order By: Relevance
“…were obtained in this study, greater antifungal activity was anticipated. Zeolite and montmorillonite had uniformly distributed, smaller AgNPs, which may be attributed to their flatter matrix structures that provided a greater surface area for AgNP adhesion [39,40] . Compared to zeolite and montmorillonite, palygorskite had fibrous rod structures, resulting in a lower surface area to bind individual AgNPs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…were obtained in this study, greater antifungal activity was anticipated. Zeolite and montmorillonite had uniformly distributed, smaller AgNPs, which may be attributed to their flatter matrix structures that provided a greater surface area for AgNP adhesion [39,40] . Compared to zeolite and montmorillonite, palygorskite had fibrous rod structures, resulting in a lower surface area to bind individual AgNPs.…”
Section: Resultsmentioning
confidence: 99%
“…Zeolite and montmorillonite had uniformly distributed, smaller AgNPs, which may be attributed to their flatter matrix structures that provided a greater surface area for AgNP adhesion. [39,40] Compared to zeolite and montmorillonite, palygorskite had fibrous rod structures, resulting in a lower surface area to bind individual AgNPs. Due to this, NPs produced from palygorskite usually occur as aggregates and clusters of large-sized NPs.…”
Section: Synthesis and Characterization Of Nanosilver Clay Compositesmentioning
confidence: 99%
“…72,73 Surface modifications affect the bio-uptake and translocation of nanoparticles and studies indicate the favorable effect of imparting a positive surface potential on nano surfaces owing to the higher cellular uptake efficiency than neutral and negatively charged nanoforms. 23,24 Various analogous studies reported the size-dependent augmented uptake of positively charged inorganic metal nanoparticles with better effects. [25][26][27] Thus, the present experimental results indicate that the positive topology of ZnS nanoforms show a superior outcome as a nano fungicide and nutritional fertilizer.…”
Section: Nutritional Zn Content In Seedlingsmentioning
confidence: 99%
“…23 Positively charged nanoparticles are reported to augment the electrostatic interaction between the fungal wall glycoprotein (negatively charged), leading to morphological changes, shrinkage of the cytoplasm, disruption of DNA and RNA synthesis, and ultimately hyphal death. 24,25 Besides their in vitro potential, positive nanoforms are proven to exhibit good accumulation, distribution and assimilation in biosystems, enhancing their applications. 26,27 There are many knowledge gaps that need to be filled by agrochemists in terms of the effect of an enhancement in surface charge on pathological and phyto-quality parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Modern times has also witnessed numerous reports (Burange et al, 2021; Korkmaz, 2020; Khan et al, 2023) describing different types of biological activities of silver. Antimicrobial activity of different forms of silver has also been documented e.g., antiviral (Balasubramaniam et al, 2020; Jain et al, 2021; Ratan et al, 2021), antibacterial (Balasubramaniam et al, 2020; Ibrahim et al, 2020; Bruna et al, 2021), antifungal (Mussin et al, 2022; Matras et al, 2022), antiprotozoal (Abou Elez et al, 2023), and anthelmintic (Majumdar and Kar, 2023; Gajera et al, 2023a). Different forms of silver (e.g., metallic, colloidal, silver salts) may have different mechanisms of action, and varying magnitude of biological activity.…”
Section: Introductionmentioning
confidence: 99%